Respuesta :

the answer is (5n+6)(n-2)

Answer:

(n - 2)(5n + 6)

Step-by-step explanation:

Given

5n² - 4n - 12

Consider the factors of the product of the n² term and the constant term which sum to give the coefficient of the n- term

product = 5 × - 12 = - 60 and sum = - 4

The factors are - 10 and + 6

Use these factors to split the n- term

5n² - 10n + 6n - 12 ( factor the first/second and third/fourth terms )

= 5n(n - 2) + 6(n - 2) ← factor out (n - 2) from each term

= (n - 2)(5n + 6) ← in factored form

ACCESS MORE